Computational study on the reduction and solvolysis of triplet chlorobenzenes. (26th September 2022) - Nitu, Cristina; Crespi, Stefano
Abstract: In this work we explored the excited state reactivity of triplet chlorobenzenes with density functional theory and a cluster‐continuum approach. We modeled two competing reactions: a direct abstraction of hydrogen from a solvent molecule and solvolysis via photo‐SN 2Ar. Electron donating (–OMe, –CH2 SiMe3, –SiMe3 ) and withdrawing (–CN) substituents not only have distinct effects on the triplet geometries, inducing structural distortions due to the relief of excited state antiaromaticity, but also affect the reactivity of the system. Therefore, electron‐rich chlorobenzenes favor the radical reduction, while electron deficiency opens the possibility for solvolysis. Both reactions are energetically comparable to or more favorable then the dissociation of the C‐Cl bond to form triplet or singlet aryl cations, the intermediates considered responsible for these reactivities. Our findings can be correlated with experimental results on similar systems available from the literature, deeming the proposed pathways as viable alternatives to established mechanisms involving aryl cations. Abstract : Substituted chlorobenzenes are believed to undergo photochemical reduction and solvolysis via triplet and singlet aryl cations' intermediates. We propose two alternative mechanisms for these photochemical reactions, involving bimolecular transition states on the triplet surface. A computational study with density functional theory and the cluster‐continuum approach was performed on several chlorobenzene derivatives containing electron‐donating ( p ‐OMe, p ‐CH2 SiMe2, o ‐SiMe3 ), electron‐neutral ( p ‐H), and electron‐withdrawing ( p ‐CN) groups. Comparison of the calculations with literature and experimental data rendered the proposed pathways as viable mechanistic options.